Evaluation of the Policy for Providing BLT Village Funds for Overcoming the Impact of the COVID-19 Pandemic in Tirto District, Pekalongan Regency - Hendika Dwinanda Wicaksana; Budi Setiyono; Rina Martini (Jurnal Public Policy, 2022)
The COVID-19 pandemic has forced the government in the Villages of Pacar and Dadirejo, Tirto Sub-district, Pekalongan Regency to use village funds to become BLT Village Funds to help communities affected by the pandemic. The purpose of this study is to evaluate the ongoing BLT Dana Desa policy. This study uses an exploratory qualitative approach, which describes in depth the policy of the Village Fund BLT in the Villages of Pacar and Dadirejo. data collection methods through interviews and documentation. As a result, the Pacar and Dadirejo governments did not succeed in implementing the Village Fund BLT policy properly, this was based on the public policy evaluation indicators from William N Dunn, such as effectiveness, efficiency, adequacy, equity, responsiveness.